BASIC CONCEPTS OF THE THEORY OF UNCERTAIN SETS AND ACTIONS RELATED TO INVESTMENT PROCESSES - Bakhriddin Juraevich1, Maxmudov; Mansurjon Mardonakulovich, Bustonov; Bahromjon Ibroximovich, Rakhimov (International Journal of Business, Law, and Education, 2021)
The theory of ambiguous collections is a new approach to expressing business processes, and there is uncertainty that undermines and complicates even precise quantitative methods and approaches. In this sense, it is possible to include linguistic variables in the analysis as the main distinguishing features of vague collection theory.